Evaluación de la funda protectora impregnada con Bifentrina sobre el daño de la "mancha roja" causado por Chaetanaphotrips signipennis en banano - León Tigrero, Jonny Christopher (2018)
VIII. SUMMARY It is imperative to find methods that limit the damage caused by the thrips of the red spot in banana plantations, this research is proposed setting as a general objective "To evaluate the effectiveness of the protective cover of the cluster impregnated with 0.1% Bifenthrin on the damage of the red spot" "caused by thrips Chaetanaphotrips signipennis in banana", and as specific objectives: 1) Determine the most effective and economical treatment of Bifenthrin concentrations; 2) Determine the yield of each of the applied treatments of the fruit; 3) Evaluate cost and benefits of the treatments, 4) Visualize possible phytotoxic effects of the different concentrations of Bifentrina on the fruit. The work was carried out at the hacienda "La Flor de Madura" owned by Mr. Harry Salazar Pino, located in the parish of Bejucal Island of the Baba canton, Los Ríos Province, with the geographic coordinates X: 0649315; Y: 9511168. The experimental area has a height of 17, humid tropical climate, with an average annual temperature of 25.4 annual average precipitation of 1262mm, relative humidity of 75% and 987.1 hours of average annual heliophilous. For this trial the Design of Complete Blocks at Random was used with 5 treatments and 4 repetitions, which will originate a total of 20 experimental units. The treatments included the use of simple untreated polyethylene covers and covers treated with Bifenthrin. Once the respective analyzes were carried out, it was concluded that the best option for the producer is the use of the covers treated with Bifenthrin 0.1%, showing an efficiency percentage of 80% at 45 and 90 days, qualifying it as an alternative to reduce considerably the presence of the insect, as the severity of the damage in the cluster.